Analysis of grain growth, structural and magnetic properties of Li-Ni-Zn ferrite under the influence of sintering temperature. Issue 2 (February 2019) - Islam, M.A.; Rahaman, M. Zahidur; Hasan, Md. Mehedi; Hossain, A.K.M. Akther
Abstract: The effect of sintering temperature (TS ) on the structural and magnetic properties of Li 0.15 Ni 0.3 Zn 0.4 Fe 2.15 O 4 is investigated and discussed. The sample is synthesized by the sol-gel auto combustion method and sintered at 1373–1573 K for 5 h. Phase identification of the powder sample was performed by using the X-ray diffraction (XRD). The XRD patterns confirmed the formation of single phase cubic spinel structure. The bulk density is correlated with TS . From the energy-dispersive X-ray spectroscopy study, it is observed that the percentage of the elements in the component phases is well consistent with the nominal composition of the composites. Field Emission Scanning Electron Microscopy showed that the average grain size (D) is increased with increasing TS . The frequency (100 Hz–120 MHz) dependent complex initial permeability spectra and relative quality factor increased with sintering temperature up to 1523 K then decreased for further increase in temperature. The complex initial permeability has been explained with the help of microstructure, and the redistribution of cations in their sites.